Developing family‐centred care in a neonatal intensive care unit: an action research study protocol. (28th December 2015) - Skene, Caryl; Gerrish, Kate; Price, Fiona; Pilling, Elizabeth; Bayliss, Pauline
Abstract: Aim: The aim of this study was to develop, implement and evaluate evidence‐based family‐centred interventions and to promote parental involvement in the care of infants in neonatal intensive care. Background: Parental involvement in the care of their infants in Neonatal Intensive Care Units leads to improved neonatal outcomes. Although research identifies the benefits of individual interventions to promote family‐centred care, little is known about how they might be implemented in everyday practice. Design: Participatory action research. Methods: Funding commenced in January 2015. The study comprises three phases: (i) Exploration: Baseline measures of staff and parental satisfaction with care and parental stress will be obtained using validated survey instruments. Baseline infant data includes breast feeding and skin‐to‐skin contact. Staff focus groups and interviews will provide insight into the context of parental involvement and perceived barriers to change. Parent focus groups and diaries will provide insight into factors influencing parental involvement in care. The data will inform the development of the evidence‐based intervention; (ii) Intervention: Three action research cycles and ongoing data collection from parents and staff will inform the further development of the intervention and change process; (iii) Evaluation: Baseline measures will be repeated to identify changes. Focus groups and interviews with staff and parents will provide insight into their perceptions of the success of the initiative in promoting family‐centred care. Discussion: This study will contribute new knowledge about approaches to actively involve parents in the care of their infant on neonatal intensive care units. Greater understanding of the impact of family‐centre care on staff and parents will be gained with the potential to inform future policy and practice.